THE ROLE OF BITUMEN IN STRATA-BOUND COPPER DEPOSIT FORMATION IN THE COPIAPO AREA, NORTHERN CHILE - Cisternas M.E.; Hermosilla Ju. (My University, 2006)
In northern Chile, between 27 and 33°S, there are numerous deposits where residual petroleum is associated with Cu-(Ag) mineralisation (the most famous being El Soldado). All of these deposits are hosted by Lower Cretaceous volcanic or volcanoclastic facies along the axis of a former backarc basin. This close relationship suggests that the generation, migration and emplacement of hydrocarbons in the Cretaceous volcanic units is a regional process, associated with the evolution of the Cretaceous backarc basin and points to the importance of pyrobitumen as an exploration tool for similar Cu–(Ag) deposits. The present work analyses four small strata-bound copper deposits located along a north–south belt approximately 10 km east of Copiapó in northern Chile. These deposits are typically hosted by pyrobitumen-rich andesitic volcanic to volcanoclastic rocks intercalated with the marine carbonate Pabellón Formation, the youngest formation within the Chañarcillo Group. The strong genetic and spatial relationships between the pyrobitumen-rich lavas and the mineral deposits allow us to define this volcanic belt as the Ocoita-Pabellón Metallotect. Two hydrothermal events can be distinguished based on the mineralogical, textural, fluid inclusion and isotope data of ore and gangue and on the optical properties of residual petroleum. During the early event, petroleum was mobilised from the source rocks into the primary and secondary porosity of the lavas by Fe-rich hydrothermal fluids, which precipitated pyrite as an early sulphide phase. The second event is characterised by Cu-rich hydrothermal fluids, which induced three successive sub-stages of Cu-sulphide precipitation. The hydrothermal fluids chemically and thermally altered the first-stage bitumen, transforming it into pyrobitumen. The present work documents similarities between the Ocoita-Pabellón Metallotect and the El Soldado ore deposit and emphasises important differences. In the El Soldado host rocks, a petroleum reservoir existed prior to the arrival of the mineralising hydrothermal fluids, the framboidal pyrite was formed by assistance of bacteria, the S of the Cu sulphides was inherited from the pyrite, and the fluid source was basin connate-metamorphic brine. In the Ocoita-Pabellón Metallotect, the hydrocarbons were mobilised into the host rocks by hydrothermal fluids; the pyrite is epigenetic, the δ34S values of pyrite and copper sulphides are very different, with distinctive light δ34S signature of Cu sulphides (δ34S between −44.7 and −17.9‰), and the calculated δ18O of hydrothermal fluids indicates the participation of meteoric water in the late phases of the hydrothermal system.
Keywords: STRATA-BOUND CU DEPOSITS; PYROBITUMEN; STABLE ISOTOPES; VOLCANIC-HOSTED; EARLY CRETACEOUS; CHILE; Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая